A study on perception of Muslim employees in Kota Bharu Kelantan toward non-participation of Zakat on income / Nor Shakimma Abu Bakar - Abu Bakar, Nor Shakimma (2013)
Zakat is synonym with purification. Purifying wealth is an obligatory to the Muslims and is done through the payment of Zakat. Unfortunately nowadays Muslims are not aware on the obligation in contributing Zakat especially Zakat on income. Furthermore, the amount collected is relatively small compared to the income tax collections. Hence, the purposes of this study are to investigate the factor that cause to the non-participation of Zakat on income based on the Muslim employee‟s perceptions. For the objectives of this study is to investigate the relationship between income level, attitude toward Zakat, level of knowledge and lack of motivation with the perception of Muslim employees in Kota Bharu Kelantan toward non-participation of Zakat on income. For the research methodology, researcher use primary data by conduct a survey (questionnaire).The sample was collected from 120 of Muslim employees in Kota Bharu Kelantan area by using convenience sampling techniques. All the data or input that gain from the questionnaire, analyzed through the SPSS (Statistical Package for the Social Sciences) software version 20.0 for obtaining the accurate result. In order to determine the significance relationship of all the four variables which is income levels, attitude toward Zakat, level of knowledge and lack of motivation, this study has used regression analysis which comprised of Analysis of Variance (ANOVA),Multiple Regression Model, Coefficient Of Correlation(R),Coefficient of Determination(R2),P-Value Approach, and also Durbin Watson Statistic. The results of the finding state that the income level, attitude toward Zakat, and level of knowledge has significant relationship with the perception of Muslim employees toward non-participation of Zakat on income. Whereas for the lack of motivation its show no significant relationship between the perception of Muslim employees in Kota Bharu Kelantan toward non-participation of Zakat on income. From the findings and after do this study, it can be concluded that Muslim employees in Kota Bharu Kelantan aware with the non-participation of Zakat on income issues. Furthermore, most of the respondents are strongly agree with the mean of acceptance is 7.4200. Even though most of the respondents are come from the Zakat payer, but there are still have a portion of non-participation of Zakat on income with the valid percentage is 30% from this study. Meaning that, overall of the respondents are agreed with the higher mean acceptance of the non-participation of Zakat on income issues